Political power : the development of the field - Haugaard, Mark, 1961-; Ryan, Kevin (The world of political science : the development of the discipline, 2012)
Although the concept of power is central to the study of politics, there is no agreement as to what exactly power is. Power is often viewed negatively, as domination, though it is also the case that power is created by people acting in concert, in which case it can have positive effects. Making sense of this puzzle is one of the aims of this book, which provides the reader with a clear and coherent way of understanding the various forms and manifestations of power, and it does so by bringing together the most important and influential perspectives on power within the political and social sciences. From the Contents: Mark Haugaard and Kevin Ryan: Power in Social and Political Theory John Gledhill: Power in Political Anthropology Stewart Clegg: Foundations of Organizational Power Jill Vickers: Gendering Power: Feminist Approaches John A. Hall and Siniša Maleševic: The Political Sociology of Power Philip G. Cerny: Power and International Relations